Electrostatics choreographs the aggregation dynamics of full-length TDP-43 via a monomeric amyloid precursor - Doke, Abhilasha A.; Jha, Santosh Kumar (Biochemistry, 2024)
TDP-43 is a ubiquitously expressed, multidomain functional protein that is distinctively known to form aggregates in many fatal neurodegenerative disorders. However, the information for arresting TDP-43 aggregation is missing due to a lack of understanding of the molecular mechanism of the aggregation and structural properties of TDP-43. TDP-43 is inherently prone to aggregation and has minimal protein solubility. Multiple studies have been performed on the smaller parts of TDP-43 or the full-length protein attached to a large solubilization tag. However, the presence of co-solutes or solubilization tags is observed to interfere with the molecular properties and aggregation mechanism of full-length TDP-43. Notably, this study populated and characterized the native, dimeric state of TDP-43 without the interference of co-solutes or protein modifications. We observed that the electrostatics of the local environment is capable of the partial unfolding and monomerization of the native dimeric state of TDP-43 into an amyloidogenic molten globule. By employing the tools of thermodynamics and kinetics, we reveal the structural characteristics and temporal order of the early intermediates and transition states during the transition of the molten globule to beta-rich, amyloid-like aggregates of TDP-43, which is governed by the electrostatics of the environment. The current advanced understanding of the nature of native and early aggregation-prone intermediates, early steps, and the influence of electrostatics in TDP-43 aggregation is essential for drug design.